Clinical and Laboratory Profiles of Children with West Syndrome: Experience of 50 Cases in a Tertiary Hospital in Bangladesh (Bangladesh Journal of Child Health, 2021)
Background: West Syndrome (WS) consists of epileptic spasms, hypsarrhythmia on EEG and psychomotor delay or regression in children.Objective: To observe the clinical and laboratory profiles of children with west syndrome.Materials & Methods: This was a cross sectional study and done from July 2017 to June 2018 in Pediatric Neurology OPD, NINS among total 50 cases of WS (age of > 2 month to 2 years). WS was diagnosed by direct observation or video recording of spasm, along with history of developmental delay or regression and EEG change. Collected data regarding demography, detailed of spasm, clinical examination, radiological and EEG findings were analyzed.Results: Mean age of the patients was 12.61 ± 7.11 months. Males (58.0%) were predominant than females (42.0%). Mean age of onset of spasm was 5.88 ± 3.73 months. Type of spasm: Flexor in 88.0% cases, extensor in 6.0% cases, mixed in 4.0% and asymmetric in 2.0%. Microcephaly was present in 90.0% cases and in 64% cases H/o perinatal asphyxia (PNA) was present. In EEG, Hypsarrhythmia was found in 62.0% cases and modified hypsarrhythmia in 38.0% cases. In CT scan of brain, cerebral atrophy was found in 62.5.0% cases, stroke in 6.0% cases. Out of all WS patients 82% were symptomatic and 18% were either cryptogenic or idiopathic.Conclusion: Flexor type spasm was found more commonly in West syndrome. History of perinatal asphyxia (PNA) was present in majority of cases. In EEG findings, hypsarrhythmia was found more than modified hypsarrhythmia.Bangladesh J Child Health 2020; VOL 44 (3) :139-142